Likelihood of Aortic Valve Preservation During Repair of Acute Type A Aortic Dissection. Issue 5 (May 2020) - Thornhill, Rosanne; Shih, Wendy; Amen, Marvin I.; John, Mohan M.; Floridia, Rosario; Razzouk, Anees J.; Rabkin, David G.
Background: We sought risk factors for replacement of the aortic valve with or without the root (AVR/root) in the setting of acute type A aortic dissection (ATAD) repair. Methods: All ATAD repairs at our institution from January 2005 to June 2018 were reviewed. Baseline characteristics were recorded. For patients with aortic valve preservation we documented the degree of aortic insufficiency (AI) postoperatively and on subsequent echocardiograms when available. Logistic regression was used to determine the association between preoperative characteristics and the odds ratio of AVR/root. Results: A total of 206 patients underwent repair of ATAD. Thirty-four were excluded for no documented AI grading. Forty-six underwent AVR/root during repair of the ATAD (including 40 root replacements). Of 126 that did not undergo AVR/root, 42 (33.33%) had follow-up echocardiograms at a median of 68 months postoperatively and 2 required reintervention for valve insufficiency. Increase in degree of AI, bicuspid valve morphology, size of the aortic root, and connective tissue disorder were significantly associated with increased risk of AVR/root. Of 130 patients without connective tissue disorder, bicuspid aortic valve, aortic root aneurysm, or intimal root tear, the rate of valve preservation was 65/65 (100%), 25/29 (86.2%), and 22/40 (55%) for those presenting with mild, moderate, and severe AI, respectively. Discussion: Degree of preoperative AI, bicuspid valve morphology, size of the aortic root, and connective tissue disorder significantly correlate with failure of aortic valve preservation in patients with ATAD. The vast majority of tricuspid valves in patients without connective tissue disorder or aortic root pathology can be salvaged.